Question-Answer in ‘Ayat-Ayat Cinta’ (A Study of Speech Act in Novel) - Batmang Batmang (Langkawi: Journal of The Association for Arabic and English, 2018)
This study aims to obtain information related to the forms and the uses of linkages adjacency pair of 'question-answer' used in Ayat-Ayat Cinta, as well as understand the function of the adjacent pair in establishing the integrity of the novel discourse. This study is a qualitative study which is operationally using the principles of speech act study. The speech act referred in this study is a dialogue in the novel which becomes the data source of this research. Data was collected by the following procedure: (1) to identify the overall dialogue in the novel; Ayat-Ayat Cinta; (2) to determine the adjacent pair in the form of "questions-answers."; (3) to find the forms and the links between each pair of utterances focused on "question-answer” type. The research findings indicate that the adjacent pairs of "question-answer" are found in the following forms: (1) short sentences; (2) ellipsis (3) deep structure; and (4) informal language (slang). The function of the adjacency pairs of "question-answer" in this novel are as controlling the integrity of discourse, namely (1) to express pleasure/choice of the characters; (2) to explain the identity, background and character of the characters; and (3) to reveal the history of the past of the characters.